2019
DOI: 10.1186/s12862-019-1469-1
|View full text |Cite
|
Sign up to set email alerts
|

GC content of vertebrate exome landscapes reveal areas of accelerated protein evolution

Abstract: Background Rapid accumulation of vertebrate genome sequences render comparative genomics a powerful approach to study macro-evolutionary events. The assessment of phylogenic relationships between species routinely depends on the analysis of sequence homology at the nucleotide or protein level. Results We analyzed mRNA GC content, codon usage and divergence of orthologous proteins in 55 vertebrate genomes. Data were visualized in genome-wide landscapes using a sliding wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The currently most plausible findings link the genome GC content with the chromosome size and with life history traits, where the effective population size (Ne) is the most important indicator of the strength of the gBGC [ 18 , 20 ]. For fish, there is no systematic analysis of GC% based on purely genomic data as are available for mammals [ 20 , 21 , 22 ], birds [ 23 , 24 ], and reptiles [ 25 , 26 ]. One study assessing GC% based on non-genomic determination showed a slightly higher GC% in marine and migrating marine fish species [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently most plausible findings link the genome GC content with the chromosome size and with life history traits, where the effective population size (Ne) is the most important indicator of the strength of the gBGC [ 18 , 20 ]. For fish, there is no systematic analysis of GC% based on purely genomic data as are available for mammals [ 20 , 21 , 22 ], birds [ 23 , 24 ], and reptiles [ 25 , 26 ]. One study assessing GC% based on non-genomic determination showed a slightly higher GC% in marine and migrating marine fish species [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the chromosome or chromosome arm size plays an important role as there is at least one crossing-over (i.e., one recombination event) per one chromosome arm in bi-armed chromosomes and per chromosome in mono-armed chromosomes [ 18 , 19 ]. Among vertebrates, the efficiency of gBGC on the GC% has been investigated in great detail mostly in the coding (i.e., exonic) regions and above all in mammals [ 20 , 21 , 22 ] and birds [ 23 , 24 ], but also in reptiles [ 25 , 26 ]. The same applies for the online available GCevobase, an evolution-based database for the GC content in eukaryotic genomes displaying GC contents for all the annotated coding sequences from Ensembl [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive amount of research has been dedicated to our understanding of protein sequence evolution, and what may enable adaptation without disrupting already present biological functions. The functional divergence of genomes has been explored by studying gene duplication 2 4 , de novo gene emergence 5 10 , open reading frame extension 11 13 , and sequence properties 14 , 15 , i.e., GC-content 16 and codon usage 17 – 19 . While there has been much focus on addressing wherefrom and how novel sequence features emerge (e.g., gene duplication, de novo gene emergence), limited attention has been given to how novelty may become integrated into the cellular apparatus from a systems-level perspective and what systems-level processes facilitate the incorporation of novel interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we proposed a method that facilitates genome-wide analysis of macro-evolutionary events in vertebrates [1]. We used a sliding window approach, which integrates information of a centered gene and its 100 neighbors, smoothening the known erratic behavior of individual genes that vary greatly in nucleotide composition, intron size and rate of evolution of encoded proteins [1]. Such integration visualizes strong region-specific events that apply to tens or hundreds of adjacent genes.…”
Section: Introductionmentioning
confidence: 99%